PENGGUNAAN PUPUK NITROGEN DAN BIOCHAR TERHADAP PERTUMBUHAN TANAMAN SAWI PAKCOY (Brassica rapa L.) DI TANAH VERTISOL - Redu, Silas Tanggu; Adisarwanto, Titis; Sumiati, Astri (Fakultas Pertanian, 2017)
This research was aimed to determine the dose of nitrogent fertilizer usage and the procedure to apply biochar to the growth of the mustard pakcoy plants (Brassica rapa L.) on vertisol soil. This research was conducted in Dukuh Kraguman, Tegalwaru village, Dau district of Malang regency in East Java province and this research was conducted from September to November 2016. The experiment was groups random design (RAK) which consists of 13 treatments with three times repetitions. The observation was conducted three times on 25 DAP (Days After Planting), 35 DAP and 45 DAP which parameters to be observed including height, the width of the leaf, wet and dry weight of mustard pakcoy plants. The result showed that the usage of nitrogent fertilizer approximately 150 kgs urea/ha and biochar that is submerged into the dug hole increased the wet weight of plant on 25 DAP. The application of nitrogent fertilizer 100 kgs urea/ha was the optimum dose to the increasing of height, the width of the leaf, wet and dry weight of mustard pakcoy plants presentation compared to the plants without nitrogen fertilizer applied. The more the dose of the nitrogen was, the less the growth of the plants. The application of 30 tons/ha biochar equally under the soil was the best procedure to increase the height, the width of the leaf, wet and dry weight of mustard pakcoy plants presentation compared to the application of 30 tons biochar that is submerged into the dug hole or without biochar. Tujuan dari penelitian ini untuk menentukan penggunaan dosis pupuk nitrogen dan cara pemberian biochar terhadap pertumbuhan tanaman sawi pakcoy (Brassica rapa L.) pada tanah vertisol. Penelitian dilaksanakan di Dukuh Kraguman, Desa Tegalwaru, Kecamatan Dau, Kabupaten Malang, Provinsi Jawa Timur, selama tiga bulan mulai September ? November 2016. Percobaan disusun dalam Rancangan Acak Kelompok (RAK) dengan 13 perlakuan dan diulang sebanyak 3 kali. Pengamatan dilakukan 3 kali yaitu umur 25 HST, 35 HST, 45 HST dengan parameter yang diamati meliputi tinggi, luas daun, bobot basah, dan bobot kering tanaman sawi pakcoy. Hasil penelitian menunjukkan bahwa penggunaan pupuk nitrogen 150 kg urea/ha dan biochar ditugal meningkatkan bobot basah tanaman pada umur 25 HST. Pemberian pupuk nitrogen 100 kg urea/ha merupakan dosis optimum peningkatan persentase pertambahan tinggi, luas daun, jumlah daun, bobot basah dan bobot kering tanaman sawi pakcoy dibandingkan tanpa nitrogen. Semakin meningkat dosis pupuk nitrogen, persentase pertumbuhan tanaman semakin menurun. Pemberian biochar 30 ton/ha dengan cara disebar merata dalam tanah merupakan cara terbaik untuk meningkatkan persentase pertambahan tinggi, luas daun, jumlah daun, bobot basah dan bobot kering tanaman sawi pakcoy dibandingkan biochar 30 ton cara ditugal maupun tanpa biochar.